Design and development of a web-based compensation information and registration system using biometric fingerprint approval delivery using telegram bot digital: registration and submission of compensation using the fingerprint and telegram websites - Dali, Sri Wahyuni; Hadiwiyatno, Hadiwiyatno; Illahi, Dika Wahyuneng (Politeknik Negeri Malang, 2023)
Compensation is an activity carried out by students outside class hours as a sanction for the student's absence from attending scheduled lectures. In this era, information is really needed, especially information on compensation in lectures. Initially compensation on digital telecommunications networks was still done manually or by coming directly to the admin to ask about compensation. But after this system is created, it will improve the compensation system on digital telecommunications networks. Students only need to access the website and no longer need to come to campus to find out information about compensation. The website has been designed in such a way to make things easier for students. This system is very useful for students because all compensation matters can be done via the website so it will be more effective for students. The problem with the Digital Telecommunication Network Study Program is that 84% of students have not compensated and only 16% of students have compensated. Based on these problems, development was carried out in the form of designing a web-based compensation information and registration system using biometric fingerprints for sending compensation agreements using a telegram bot. The information system used is a series of biometric systems with fingerprint sensor devices with FPM10A module, Telegram Bot, Arduino and ESP32 features and produces a system prototype that can provide information about compensation and compensation registration to polynema students so that it can make things easier for students of the Digital Telecommunication Network Study Program Malang State Polytechnic in paying compensation